(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
This article examines the extensive influence of the English language on other languages worldwide, particularly focusing on vocabulary, syntax, and cultural expressions. The global status of English as a lingua franca in business, technology, science, and entertainment has led to its pervasive integration into various linguistic and cultural contexts. This integration has brought both enrichment and challenges, impacting local languages through the adoption of English loanwords, shifts in grammar, and changes in communicative practices. Analyzing examples from multiple languages, this study highlights how English contributes to linguistic diversity while simultaneously raising concerns about language preservation and cultural identity. The article underscores the significance of finding a balance that embraces the benefits of English influence while safeguarding linguistic heritage.